Place-making of ecotourism in Tasik Chini: From exploratory to the contemporary biosphere reserve - Mohd Ekhwan, Toriman (2013)
Place-making is crucial in tourism destination as how it evolves and develops over time plays a significantly role in destination's sustainability. As ecotourism is often perceived as an excellent tool for promoting sustainable development, including in the Biosphere Reserve (BR), any initiatives in promoting this destination, thebibore, have to be in a responsible manner, representing a real experience of the destination. While there is copious of literature on ecotourism in the BRs, no research has been conducted on how place-making of ecotourism in Tasik Chini from its evolution to the current status of Biosphere Reserve. Taking into account the needs of place-making that fits the aspiration of a sustainable destination, this article aims to analyze how place-making of Tasik Chini evolved and being developed in the life cycle of Tasik Chini as an ecotourism destination, aiming at tracing on travel engagement and ecotourism experiences. The study reveals four major components that drive the place-making of ecotourism in Tasik Chini, from exploratory to contemporary towards achieving sustainable development: the state of ecotourism in the BR, who the segments are, involvement of community and the government intervention and support system. It is imperative an integrated place-making of ecotourism destination be promoted and enhanced by all stakeholders in the future undertaking.